Exchange-rate overshooting: An analysis for intermediate macro - Fidelina B. Natividad-Carlos (University of the Philippines, School of Economics (UPSE), 2014)
While exchange rate dynamics is an important topic in open economy macroeconomics, the standard tool commonly used to introduce exchange rate dynamics - the Dornbusch (1976) seminal paper along with phase diagram - is not well-suited for undergraduate students as most of them do not have yet a background on dynamic macroeconomic analysis. This paper attempts to provide a graphical device - a panel IS*-LM* diagram - which can be used to teach intermediate macroeconomics students about Dornbusch's idea of exchange rate dynamics. In addition, it also attempts to bridge the gap between undergraduate teaching and graduate teaching of exchange rate dynamics by showing the correspondence between the economy's adjustment path in the IS*-LM* diagram and that in the phase diagram.
Keywords: A15; A23; F31; F41; 330; undergraduate teaching; graduate teaching; exchange rates; exchange rate dynamics; sticky prices; interest parity; open economy macroeconomics; fiscal policy; monetary policy